2021
DOI: 10.3168/jds.2020-19675
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E analogs limit in vitro oxidant damage to bovine mammary endothelial cells

Abstract: Diseases that occur during the transition period are exacerbated when cows are unable to cope with an increased pro-oxidant load that results in oxidative stress. Dairy cattle are routinely supplemented with the vitamin E analog α-tocopherol to mitigate the severity of oxidative stress. Nonetheless, oxidative stress remains a disease predisposing condition for many dairy cattle. A better method of optimizing the antioxidant functions of vitamin E is needed. α-Tocopherol is only 1 of 8 analogs of vitamin E, all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…The same study also showed superior antioxidant effects of the tocopherols compared to the tocotrienol counterparts. 310 The metabolism of both tocopherol and tocotrienols undergo a similar process although the tocotrienols degrade in a more complex manner. In vitro differences have been observed in a HepG2 cell culture model although it was postulated to be different in in vivo systems.…”
Section: Ramifications Of Therapeutic Usementioning
confidence: 99%
“…The same study also showed superior antioxidant effects of the tocopherols compared to the tocotrienol counterparts. 310 The metabolism of both tocopherol and tocotrienols undergo a similar process although the tocotrienols degrade in a more complex manner. In vitro differences have been observed in a HepG2 cell culture model although it was postulated to be different in in vivo systems.…”
Section: Ramifications Of Therapeutic Usementioning
confidence: 99%
“…Elevated IsoP production is an indicator for oxidative stress, or damage to healthy tissue by free radicals, such as ROS. Even though the effect of IsoP on bovine vascular endothelial cells remains elusive [ 22 ], increased ROS production is associated with endothelial dysfunction [ 23 ]. Elevated IsoP production associated with addition of 1 and 5 µM AEA may therefore be a key contributor to decreased TER observed at these concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Vit E can decrease ischemia-reperfusion tissue damage (26). Some investigators have shown that small vessels' killed endothelium will enhance after the Vit E regime (27,28). Vit E regime therapy controls neoplasms growth and protects against chemotherapic side effects (29).…”
Section: Discussionmentioning
confidence: 99%